2017
DOI: 10.1021/acs.biochem.6b01027
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid P Component (SAP) Interactome in Human Plasma Containing Physiological Calcium Levels

Abstract: The pentraxin serum amyloid P component (SAP) is secreted by the liver and found in plasma at a concentration of approximately 30 mg/L. SAP is a 25 kDa homopentamer known to bind both protein and nonprotein ligands, all in a calcium-dependent manner. The function of SAP is unclear but likely involves the humoral innate immune system spanning the complement system, inflammation, and coagulation. Also, SAP is known to bind to the generic structure of amyloid deposits and possibly to protect them against proteoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…5 Although the exact function of SAP is unclear, it is known to interact in plasma with a wide variety of proteins, including complement components, apolipoproteins, and regulators of coagulation and proteolysis. 6 It forms stable calcium-dependent interactions with its ligands, including proteins, lipoproteins, and DNA, protecting them against degradation. SAP serves as a soluble pattern-recognition molecule involved in the innate immune response, recognizing a variety of pathogen-and damage-associated molecular patterns, including microbial components and apoptotic cell debris.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Although the exact function of SAP is unclear, it is known to interact in plasma with a wide variety of proteins, including complement components, apolipoproteins, and regulators of coagulation and proteolysis. 6 It forms stable calcium-dependent interactions with its ligands, including proteins, lipoproteins, and DNA, protecting them against degradation. SAP serves as a soluble pattern-recognition molecule involved in the innate immune response, recognizing a variety of pathogen-and damage-associated molecular patterns, including microbial components and apoptotic cell debris.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation is that IgG kappa is present as c l i n i c a l i n v e s t i g a t i o n a result of a normal interaction between these 2 proteins rather than an autoimmune antigen-antibody interaction, as Ig kappa chain is known to be a part of the normal interactome of serum SAP. 6 Therefore, although useful for tissue diagnostics of this entity, testing for SAP antibodies in the serum does not serve as a noninvasive diagnostic at this time, and the underlying driver of this disease remains a mystery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, these data do not exclude SAP interaction with upstream complement components to enhance opsonization of PGN. In fact, a recent report shows that SAP interacts with multiple upstream components of the complement cascade ( 28 ). Consistent with the latter study, we found that depletion of SAP also led to partial depletion of C1q.…”
Section: Discussionmentioning
confidence: 99%
“…Serum amyloid P-component (APCS) showed increase expression in the plasma of patients with epilepsy. Serum amyloid P-component belongs to the group of short pentraxins in the pentraxin family, which is known to be involved the humoral innate immune system spanning the complement system, inflammation, and coagulation [ 25 ]. Urbanyi et al demonstrated that serum amyloid P-component induced neuronal apoptosis through penetrating the plasma membrane and translocating selectively into the nuclei of neurons [ 26 ].…”
Section: Discussionmentioning
confidence: 99%